2005
DOI: 10.1021/ie050382n
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Moisture on CO2 Separation from Gas Mixture by a Nanoporous Adsorbent Based on Polyethylenimine-Modified Molecular Sieve MCM-41

Abstract: Adsorption separation of CO2 from simulated flue gas containing CO2, O2, and N2 with and without moisture was investigated using a novel nanoporous adsorbent based on polyethylenimine (PEI)-modified mesoporous molecular sieve MCM-41 in a flow system. The CO2 adsorption capacity and CO2 separation selectivity of MCM-41 were greatly improved by loading PEI into its nanosized pore channels, which made the resulting adsorbent operating like a “molecular basket” for CO2. CO2 adsorption capacity of the MCM-41-PEI ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
355
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(380 citation statements)
references
References 26 publications
(58 reference statements)
19
355
2
4
Order By: Relevance
“…The q e of both samples increased with temperature from 20 to 60°C but decreased with temperature from 60 to 100°C and have the maximum q e at 60°C. Similar observations on the correlation of q e with temperature had been reported in other studies of silica sorbents, 21,40 where the maximum q e was found at 75°C. This may be because of the nature of silica sorbents.…”
Section: Adsorption Behaviorssupporting
confidence: 90%
“…The q e of both samples increased with temperature from 20 to 60°C but decreased with temperature from 60 to 100°C and have the maximum q e at 60°C. Similar observations on the correlation of q e with temperature had been reported in other studies of silica sorbents, 21,40 where the maximum q e was found at 75°C. This may be because of the nature of silica sorbents.…”
Section: Adsorption Behaviorssupporting
confidence: 90%
“…Xu et al (80) developed a "molecular basket" adsorbent (MCM-41-PEI) for CO 2 capture from flue gas of a natural gas-fired boiler. It is claimed to have high adsorption capacity and high CO 2 selectivity.…”
Section: Process Descriptionmentioning
confidence: 99%
“…For removal of CO 2 from flue gas, adsorption process is a very simple and cost-effective [2]. The activated carbon (AC) surface chemistry is also an important criteria [3][4] during adsorption process.…”
Section: Introductionmentioning
confidence: 99%